(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
The article examines the issues of improving the accounting policy for liabilities in enterprises in the field of information and communication technologies (ICT) based on international standards. The author has developed a model form that includes 10 main sections of the accounting policy (general rules, recognition, measurement, classification, documentation, inventory, revaluation, disclosure, risk management, internal control) and 5 special sections specific to the ICT sector (license obligations, digital services, subscriber losses, network modernization, international roaming).